Efektywność prawa umów. Rola sądów - Szczerbowski, Jakub (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Effectiveness of every contract lies in the center of interest of the parties, especially in contracts between professional entrepreneurs. Despite this law in books rarely acknowledges effectiveness as a category. Organization and functioning of the judiciary has influence on the transaction costs of contracts. This influence can be divided into two broad categories, the influence of instability or divergence of court decisions, and the influence of access to justice. It is generally concluded, that stability of court decisions influences access to justice as it minimizes incentives for disputes. A different view is proposed by E. Posner in his thought experiment, in which radically incompetent courts still compel contractual parties to perform – mainly by deterring them from using the judicial system. This paper discusses the validity of this thought experiment by questioning its assumptions and its ability to explain empirical observations.